Lucifer's daughter eaudiobook - Carpenter, Kel (Queen of the Damned, 2018)
We've all heard the story of the Four Horsemen. Harbingers of the apocalypse. Destruction given form. Four of the sexiest—wait no—forget that. You get my point. So imagine my surprise when I find out everything I've ever been told, is a lie. But we're getting ahead of ourselves here. Let's start from the beginning. My name is Ruby Morningstar. I run a tattoo parlor in Portland with my best friend, have a pet raccoon, a crazy ex that stalks me, not to mention this one little thing . . I'm a demon. Half-succubus, to be exact. For the last twenty-three years of my life, that's the story I believed, but on the day a handsome stranger bails me out of jail my world is turned upside down, and suddenly I don't know who I am anymore. Because the Four Horsemen aren't the bringers of the apocalypse. I am. Talk about never catching a break. Contains mature themes.